Secure virtualization in cloud computing - Volokyta, Artem; Kokhanevych, Igor; Ivanov, Dmytro (Видавництво Львівської політехніки, 2012)
Providing secure virtualization is an important component of cloud computing. The paper is devoted to the mechanism of monitoring of virtual machines aimed at guaranteeing increased security to cloud resources. Furthermore, the requirements for this mechanism are enumerated. A Virtual Machine Monitor which can effectively monitor guest components while remaining fully transparent to cloud users is proposed.
Keywords: virtualization; cloud computing; security